A universal strategy combining interface and grain boundary engineering for negligible hysteresis and high efficiency (21.41%) planar perovskite solar cells. Issue 13 (23rd March 2020) - Chen, Yingchu; Shi, Jie; Li, Xitao; Li, Siqi; Lv, Xinding; Sun, Xiangnan; Zheng, Yan-Zhen; Tao, Xia
Abstract : We develop a universal strategy combining interface and grain boundary engineering to effectively eliminate the hysteresis in planar PSCs. Abstract : Planar perovskite solar cells (PSCs) have the potential to compete with mesoporous PSCs due to their comparable power conversion efficiency (PCE) and their preparation, which can be achieved via similar processes to those of flexible or tandem PSCs. However, the severe current–voltage hysteresis that occurs in PSCs is still a big issue, attributable to trap-induced charge recombination and ion migration. Herein, we develop a universal strategy combining interface (PMMA:C60 ) and grain boundary (PTABr) engineering to effectively eliminate the hysteresis of planar PSCs by finely tuning the electron transport layer/perovskite interface and perovskite film morphology (grain size and grain boundary). Microstructure and spectral characterization, density functional theory (DFT) calculations and photoelectric measurements reveal that this ingenious combination of the two engineering approaches effectively reduces the trap sites and enlarges the perovskite grain size, leading to negligible hysteresis and high performance PSCs based on various compositional perovskites including MAPbI3, Cs0.15 FA0.85 PbI3 and Cs0.15 FA0.75 MA0.1 PbI3, with power conversion efficiencies (PCEs) of 18.99%, 19.82%, 21.41% and extra-low hysteresis indices of 0.011, 0.007, 0.005, respectively. This work demonstrates a universal strategy by which to fabricate high efficiency and negligible hysteresis PSCs regardless of perovskite composition.